Ek meneer en jy meneer: hoe word master dan gesmeer? - Botha, W.F. (Lexikos, 1995)
A New Approach to the Treatment of Racist Lexical Items Views on the treatment of racist lexical items are marked by the two extreme viewpoints of exclusion and inclusion with exhaustive treatment. Exclusion may be judged by posterity as falsification of history and inclusion with exhaustive treatment as insensitivity. The article focuses on a new approach in the way of inclusion with limited visible treatment. Racist lexical items are included in the printed dictionary, but with limited and sensitive treatment. An exhaustive treatment in electronic format is however available to the dictionary user on request.